Spatial-temporal soil-water content dynamics in toposequences with different plant cover in a tropical semi-arid region - Makeison Moreira de Sousa, Marcos (Revista Ciência Agronômica, 2021)
Anthropogenic effects on the natural environment and on soil moisture in the tropical semi-arid region have not yetbeen determined. As such, the temporal variability of soil moisture was investigated in two toposquences under different types ofplant cover: i) Caatinga under regeneration since 1978 (CReg); ii) Caatinga thinned by 40% (CThn). The research was carried outin two catchment located in the northeast of Brazil, with an area of 2.06 and 1.15 ha for CReg and CThn respectively. Soil moisturewas determined using the gravimetric method. Three random soil samples were collected daily from the upper, middle and lowersection of each catchment, giving a total of nine daily collections and 1620 collection in the period. CThn displayed higher valuesand a longer period for soil moisture. The lower section of the catchment showed values for soil moisture that were higher andstatistically different (p < 0.05) from the other sections. The increasing value for the correlation between moisture and the sevendays of antecedent rainfall indicates a low rate of decrease for soil moisture.